PHENOMENON OF BUYING AND SELLING AS BRIDGING ANALOGY OF LEARNING WORK AND ENERGY - Desianna, Ika; Nugroho, Sunyoto Eko; Ellianawati, Ellianawati (Physics Communication, 2019)
Effective physics learning can be designed by recognizing students' difficulties in understanding physics concepts. Students build the concept through experience gained from the environment, so that they unconsciously have the concept in accordance with the understood. Students still have difficulty distinguishing work and energy definitions in physics and in everyday life. The concept of work and energy can be understood by students if students have good analogy skills. The Brain Based Learning (BBL) model through analogy facilitates learning to improve students' thinking ability analogy. The buying and selling analogy is used to relate concepts that students have understood (source problems) to the concept of work and energy as learning goals (target problems). Quasi-experimental learning is applied to determine the analogy of students. Data were analyzed from the achievement of analogy ability test results before and after learning. The success rate of mastering students' analogy abilities is analyzed from the stages of analogy in solving problems. Achievement of pretest and posttest scores of students 'analogy abilities shows that the BBL model through buying and selling analogy can improve students' analogy skills. The average achievement of students' analogy skills at the stage of generating the analogy includes good criteria, evaluating the analogy relations stage including good criteria, understanding the analogy case stage including good criteria, and at the transfering findings, including not good criteria. The results of the analogy ability show that the BBL model through the analogy of buying and selling gives positive results on the ability of students' analogy.